Fibromuscular dysplasia of the renal arteries treated with percutaneous transluminal renal angioplasty: a case report - Yalçınkaya, Fatoş; Tümer, Necmiye; Ekim, Mesiha; Şanlıdilek, Umman (The Turkish Journal of Pediatrics, 1990)
A nine-year-old girl with renovascular hypertension is presented. The diagnosis of fibromuscular dysplasia was established by selective renal angiography, and percutaneous transluminal renal angioplasty was performed. After successful dilation, the blood pressure returned to normal. The patient has been followed for a year and there is no evidence of hypertension.
Keywords: fibromuscular dysplasia; percutaneous transluminal renal angioplasty